The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1590/s1516-18462010005000025
|View full text |Cite
|
Sign up to set email alerts
|

Otite média recorrente e habilidade de localização sonora em pré-escolares

Abstract: RESUMOObjetivo: comparar o desempenho de 40 pré-escolares no teste de localização sonora com as respostas de seus pais para um questionário que investigou a ocorrência de episódios de otite média (OM) e os sintomas indicativos de desordens audiológicas e do processamento auditivo. Métodos: após aplicação e análise das respostas do questionário, dois grupos foram formados: GO, com histórico de OM, e GC, sem este histórico. Cada grupo com 20 pré-escolares de ambos os gêneros foi submetido ao teste de localização… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 22 publications
0
5
0
3
Order By: Relevance
“…Vanessa Vieira Farias (1) , Elizangêla Dias Camboim (2) , Marisa Frasson de Azevedo (3) , Lauralice Raposo Marques (4) (1) Speech graduated from State University of Health Sciences of Alagoas -UNCISAL, Maceió, Alagoas. (2) Audiologist, Assistant Professor, School of Speech -UNCI-SAL, Maceió, Alagoas, Expertise in Audiology.…”
Section: Ocorrência De Falhas Na Triagem Auditiva Em Escolaresmentioning
confidence: 99%
See 2 more Smart Citations
“…Vanessa Vieira Farias (1) , Elizangêla Dias Camboim (2) , Marisa Frasson de Azevedo (3) , Lauralice Raposo Marques (4) (1) Speech graduated from State University of Health Sciences of Alagoas -UNCISAL, Maceió, Alagoas. (2) Audiologist, Assistant Professor, School of Speech -UNCI-SAL, Maceió, Alagoas, Expertise in Audiology.…”
Section: Ocorrência De Falhas Na Triagem Auditiva Em Escolaresmentioning
confidence: 99%
“…(2) Audiologist, Assistant Professor, School of Speech -UNCI-SAL, Maceió, Alagoas, Expertise in Audiology. (3) Speech; PhD in Human Communication Disorders, UNI-FESP, São Paulo, SP.…”
Section: Ocorrência De Falhas Na Triagem Auditiva Em Escolaresmentioning
confidence: 99%
See 1 more Smart Citation
“…It is realized through the structures of the Central Nervous System pathways, especially at the level of the brainstem and auditory cortex. As both ears receive the sound simultaneously, the first stimulated one indicates the direction of the sound source (13) . In this work, the emphasis on auditory processing in the age between 4 and 5 years and 11 months old is intended to highlight its association with the development of language and family environment, and the importance of the diagnosis of changes in this capacity of the Central Nervous System and consequent intervention.…”
Section: Introductionmentioning
confidence: 99%
“…Although this methodology has been used in similar studies 22,30 , it is suggested that in future studies the occurrence of both IVAS and otitis should be investigated objectively or clinically.…”
Section: Discussionmentioning
confidence: 99%